Kesantunan Berbahasa Dalam Pembelajaran Berkomentar - Yudyati, Rindy Loryta; , Laili Etika Rahmawati, S.Pd., M.Pd (2016)
This study had two purposes. (1) Description the forms of student's politeness on learning commented at VIIIA class, SMP Muhammadiyah 1 Gatak. (2) Description the things behind (influenced for) student politeness on learning commented at VIIIA class, SMP Muhammadiyah 1 Gatak. This type of research is descriptive qualitative. The data collection techniques used in this study is observation technique, listening and recording techniques, and deep interview. This study showed some results. (1) The student politeness forms are politeness to teacher and the other students; and the student dispoliteness forms are dispoliteness on Javanese (to teacher and the other students), dispoliteness on Indonesian (to teacher and the other students), dispoliteness on English (to teacher), and not respond to teacher. (2) The students dispoliteness is influenced by internal factor (the language ability and student's personality) and the external factor (family's basic/ area).